2020
DOI: 10.1002/hed.26077
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck treatment in sinonasal undifferentiated carcinoma: Systematic review and meta‐analysis

Abstract: Sinonasal undifferentiated carcinomas (SNUCs), being an aggressive malignancy with dismal survival outcome, have given limited consideration regarding management of regional failures. A total of 12 studies, published between 1999 and 2019, met inclusion criteria. We performed a meta-analysis assessing regional (neck) relapse after elective neck treatment compared to observation in clinically node negative (N0) necks. Clinical data of 255 patients were used for meta-analysis. Among them, 83.4% of patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…In the literature, the question of whether to perform an elective treatment on a clinical node-negative patient with SNCs remains open, and the present work may be considered as a natural prosecution of two other published meta-analyses that included only SCC [ 11 ] or SNUC [ 12 ]. Actually, squamous cell, adenocarcinomas, SNUC, and adenoid cystic carcinomas (ACC) are the most frequent histotypes that can yield nodal metastases in 28%, 25%, 12%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the question of whether to perform an elective treatment on a clinical node-negative patient with SNCs remains open, and the present work may be considered as a natural prosecution of two other published meta-analyses that included only SCC [ 11 ] or SNUC [ 12 ]. Actually, squamous cell, adenocarcinomas, SNUC, and adenoid cystic carcinomas (ACC) are the most frequent histotypes that can yield nodal metastases in 28%, 25%, 12%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of regional metastasis is notably low at the time of diagnosis (about 10% in a recently published series by Peck et al [ 9 ]), up to 33% of patients will eventually develop them during the follow-up [ 9 , 10 ]. In this regard, the decision whether to adopt a watchful waiting approach or to perform an elective neck treatment (ENT), whether by surgery (END, elective neck dissection) or radiotherapy (ENI, elective neck irradiation), on a clinically node-negative (cN0) SNC remains an understudied issue [ 11 , 12 ]. The present systematic review of the literature and meta-analysis aims to evaluate the prognostic role and clinical relevance of the elective neck treatment in the management of SNCs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several papers have suggested that elective treatment of the neck can be considered justifiable in case of advanced‐stage SCC (T3‐T4), given the relatively high incidence rate of regional failure (3‐20%) 7,8,39 . In addition, a recent meta‐analysis on sinonasal undifferentiated carcinoma showed a significantly reduced risk of regional recurrence in patients who underwent elective treatment of the neck 40 . However, the practice to not systematically perform END in sinonasal SCC is naturally shifted to the SNMM management.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,39 In addition, a recent meta-analysis on sinonasal undifferentiated carcinoma showed a significantly reduced risk of regional recurrence in patients who underwent elective treatment of the neck. 40 However, the practice to not systematically perform END in sinonasal SCC is naturally shifted to the SNMM management. However, our review demonstrated that few data are available on this topic, and the current practice should be at least reviewed.…”
Section: Discussionmentioning
confidence: 99%
“… 10 11 As such, elective neck treatment is recommended for most patients with advanced stage tumors (T3/T4), even if they present with an N0 neck. 14 …”
Section: Literature Reviewmentioning
confidence: 99%